2011
DOI: 10.2340/16501977-0814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a prolonged exercise program on key health outcomes in women with fibromyalgia: A randomized controlled trial

Abstract: Results confirm that a long-term combination of aerobic exercise, strengthening and flexibility improves psychological health status and health-related quality of life in patients with fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 30 publications
5
63
0
8
Order By: Relevance
“…It is worth highlighting that physical activity has already been considered a positive factor for QL of FM patients. In a randomized clinical trial with 42 FM patients, results have confirmed that the long term combination of aerobic, strengthening and flexibility exercises improves psychological health status and QL of such patients 22 . However, FM patients in general need a longer period and further personal effort to adapt to exercise programs and that is why load progression should be slower than normal in muscle strength exercises 23 .…”
Section: Discussionmentioning
confidence: 82%
“…It is worth highlighting that physical activity has already been considered a positive factor for QL of FM patients. In a randomized clinical trial with 42 FM patients, results have confirmed that the long term combination of aerobic, strengthening and flexibility exercises improves psychological health status and QL of such patients 22 . However, FM patients in general need a longer period and further personal effort to adapt to exercise programs and that is why load progression should be slower than normal in muscle strength exercises 23 .…”
Section: Discussionmentioning
confidence: 82%
“…This may be related to the overall lifestyle of the Chennai citizens, with the high level of religious/spiritual beliefs positively influencing both psychosocial [52] and physical well-being [53]. Similarly, the long-term exercise undertaken by the Chennai citizens may contribute to the overall better self-reported health status [54]. The benefits of regular social engagement to prevent cognitive decline have long been established, and regular attendance at religious services as a social activity may be a protective factor [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…A long-term combination of aerobic exercise, strengthening and flexibility improves psychological health status and health-related quality of life in patients with fibromyalgia (Sañudo et al, 2011). Aquatic exercise program also has showed an improvement on symptoms an anti-inflammatory effect in FM (Ortega et al, 2010).…”
Section: Therapeutic Implication Of Mitochondrial Dysfunction In Fibrmentioning
confidence: 99%